An open source plant kinase chemogenomics set. (25th November 2022) - Ercoli, Maria Florencia; Ramos, Priscila Zonzini; Jain, Rashmi; Pilotte, Joseph; Dong, Oliver Xiaoou; Thompson, Ty; Wells, Carrow I.; Elkins, Jonathan M.; Edwards, Aled M.; Couñago, Rafael M.; Drewry, David H.; Ronald, Pamela C.
Abstract: One hundred twenty‐nine protein kinases, selected to represent the diversity of the rice ( Oryza sativa ) kinome, were cloned and tested for expression in Escherichia coli . Forty of these rice kinases were purified and screened using differential scanning fluorimetry (DSF) against 627 diverse kinase inhibitors, with a range of structures and activities targeting diverse human kinases. Thirty‐seven active compounds were then tested for their ability to modify primary root development in Arabidopsis. Of these, 14 compounds caused a significant reduction of primary root length compared with control plants. Two of these inhibitory compounds bind to the predicted orthologue of Arabidopsis PSKR1, one of two receptors for PSK, a small sulfated peptide that positively controls root development. The reduced root length phenotype could not be rescued by the exogenous addition of the PSK peptide, suggesting that chemical treatment may inhibit both PSKR1 and its closely related receptor PSKR2. Six of the compounds acting as root growth inhibitors in Arabidopsis conferred the same effect in rice. Compound RAF265 (CHIR‐265), previously shown to bind the human kinase BRAF (B‐Raf proto‐oncogene, serine/threonine kinase), also binds to nine highly conserved rice kinases tested. The binding of human and rice kinases to the same compound suggests that human kinase inhibitor sets will be useful for dissecting the function of plant kinases.